2012
DOI: 10.1016/j.drugalcdep.2012.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Does the “gateway” sequence increase prediction of cannabis use disorder development beyond deviant socialization? Implications for prevention practice and policy

Abstract: Background This study was conducted to test whether non-normative socialization mediates the association between transmissible risk measured in childhood and cannabis use disorder manifested by young adulthood, and whether the sequence of drug use initiation (“gateway”, i.e., consuming legal drugs before cannabis, or the reverse) increases accuracy of prediction of cannabis use disorder. Methods Sons of fathers with or without substance use disorders (SUD) related to illicit drugs were tracked from 10–12 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 58 publications
(59 reference statements)
2
21
1
Order By: Relevance
“…This is consistent with problem behavior theory (Jessor & Jessor, 1977) and the common liability model (Vanyukov et al, 2012), and prior research (Donovan & Jessor, 1985; Donovan et al, 1988; Tarter et al, 2012). Analyses further revealed that CCR had a long-term predictive relationship with general problem behavior, which was not moderated by gender.…”
Section: Discussionsupporting
confidence: 87%
“…This is consistent with problem behavior theory (Jessor & Jessor, 1977) and the common liability model (Vanyukov et al, 2012), and prior research (Donovan & Jessor, 1985; Donovan et al, 1988; Tarter et al, 2012). Analyses further revealed that CCR had a long-term predictive relationship with general problem behavior, which was not moderated by gender.…”
Section: Discussionsupporting
confidence: 87%
“…Recently, Tarter et al(2012) presented the results of a prospective study that followed people from 10–22 years of age, which were similar to ours regarding cannabis. The most common sequence for experimenting with drugs(i.e., illegal drug use before the use of cannabis) had no effect on the problematic use of cannabis later.…”
Section: Discussionsupporting
confidence: 82%
“…This points to the existence of definite use trajectories, also called gateway sequences, which could constitute an independent risk factor for increasing use: a subject who has used a given substance is more liable to subsequent use of another substance, this subsequent use being better explained by the sequence that he (she) has entered than by opportunity for use [7] . However, the gateway hypothesis is increasingly questioned, some alternative use sequences are observed [8][9][10][11][12] , and the order of drug use initiation is not playing a substantial role in the etiology of substance use disorder (SUD) [13][14][15] . RAM was proposed to explain the reverse sequences leading from cannabis to tobacco, suggesting that the shared route by which substances are administered (e.g.…”
Section: Introductionmentioning
confidence: 99%